Knowledge Management System Adoption Approach and the Critical Success Factors in Small Medium Enterprise: A Systematic Literature Review - Ajie Tri Hutama; Dana Indra Sensuse; Sofian Lusa; Agnes Agnes (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Knowledge is a substantial factor in an organization; therefore, the successful implementation of Knowledge Management (KM) or Knowledge Management System (KMS) is important for many organizations. This applies both for large companies and for companies categorized as Small Medium Enterprise (SME). How each company finds a solution to deal with KM problems, how to adopt KMS in its company structure, and what critical success factors (CSF) must be highlighted to implement those KMS often vary depending on the size of the organization. Regarding this issue, this study aims to find out how the adoption approach and CSF are used in the implementation of KM / KMS in SME. However, this study can also improve the state-of-the-art for KM / KMS implementation in SME and the important CSF in implementing it. In this review of the literature, a systematic review was performed with the steps as follows: (1) structure the research question, (2) define inclusion-exclusion criteria, (3) evaluation of paper quality, and (4) data extraction. The study found that in the last 5 years from the time when this research is conducted, TABLE 1 which is from 2016 to 2021, SME has been using many methods like training, meeting, sharing session, repository, and research as part of their KM / KMS adoption approach. We found also in the last 5 years that the CSF for implementing KM / KMS in SME is as follows: organization structure and flexibility, organization culture towards KM adoption, the quality of the knowledge, and communication within and across areas in the organization. communication within and across areas of the organization, and the team works within and across areas of the organization. SMEs can use this research as a guide to implement KM / KMS in their organization.